POSSIBLE REGULATORY MECHANISMS IN THE OVARIAN DISORDERS - Martinek, Jindrich; Kucera, Tomas; Jirsova, Zuzana; Mlcochova, Hana; Horejsi, Jan (Biomedical papers, 2004)
...
Keywords: Human ovary/Apoptosis/Autoantibodies/Nitric oxide/Regulatory mechanisms